2017
DOI: 10.5539/ep.v6n2p6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an Authentic Historical Italian Cosmetic Talc Sample – Further Evidence for the Lack of Cancer Risk

Abstract: Italian talc from the Pinerolo Mines in North West Italy is known for its extreme purity. Several historical investigations of these mines have demonstrated very small amounts of tremolite in the host rock that occasionally found their way into the mined ore. However, more than sixty years of epidemiological studies of the Pinerolo miners and millers have failed to demonstrate any attendant cancer risk and show that this trace tremolite contamination is of no biological significance.Claims made that the Pinero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In the laboratory, talc has been shown to be contaminated with chrysotile, tremolite, and anthophyllite fibers. [34][35][36][37] Chrysotile, tremolite and anthophyllite asbestos have been shown to cause mesothelioma. 7…”
Section: Mesotheliomamentioning
confidence: 99%
“…In the laboratory, talc has been shown to be contaminated with chrysotile, tremolite, and anthophyllite fibers. [34][35][36][37] Chrysotile, tremolite and anthophyllite asbestos have been shown to cause mesothelioma. 7…”
Section: Mesotheliomamentioning
confidence: 99%
“…Moreover, the letter points to the results of Ilgren et al (2017) that showed 3.7 million tremolite fibers/gram of Italian cosmetic talc (corresponding to 0.0000722%). Additionally, Ilgren et al (2017) found no asbestos in their analysis, only non-asbestiform tremolite cleavage fragments. It is reassuring, indeed, that a robust body of epidemiological studies at Italian mines have supported this conclusion, consistently showing no association with mesothelioma and lung cancer risk (Ciocan et al, 2022;Coggiola et al, 2003;Ierardi et al, 2022;Marsh et al, 2019;Pira et al, 2017;Rubino et al, 1976Rubino et al, , 1979.…”
mentioning
confidence: 91%
“…Lastly, the studies cited in the letter (Ilgren et al, 2017;Rohl et al, 1976) are historical cosmetic talc samples, which are not relevant to our study, and we are not aware that Longo and Rigler (2019) has been published.…”
mentioning
confidence: 99%
“…In 1976, Rohl and colleagues analyzed a sample of Coty Airspun Face Powder and reported it to contain asbestos fibers in the range of 8-20% (Rohl et al, 1976). Ilgren and colleagues reported finding 3.7 million tremolite fibers per gram of talc in a container of Italian talc (Ilgren et al, 2017). American mine sources began to be used in the latter part of the 20th century.…”
mentioning
confidence: 99%